Nonlinear enhanced-absorption resonances in compact alkali-vapor cells for applications in quantum metrology. Issue 1 (March 2021) - Brazhnikov, D V; Ignatovich, S M; Mesenzova, I S; Mikhailov, A M; Skvortsov, M N; Goncharov, A N; Entin, V M; Ryabtsev, I I; Boudot, R; Taskova, E; Alipieva, E; Andreeva, C; et al.
Abstract: We review three laser spectroscopy schemes developed recently for observation of high-contrast enhanced-absorption nonlinear resonances in small alkali-vapor cells. In our experiments, optical transitions within the cesium D1 line are involved and a probe beam transmission is analyzed. The first spectroscopy method is based on the configuration with two-frequency counter propagating beams, which are linearly polarized in orthogonal directions. This configuration provides observation of high-contrast natural-linewidth resonances superimposed on broad Doppler profiles when the laser frequency is scanned. These resonances have good prospects for developing a miniature optical frequency reference. The second scheme involves two-frequency counter propagating beams with equal circular polarizations and provides observation of subnatural-linewidth resonances when the Raman frequency detuning is scanned. We use these resonances for stabilizing the microwave frequency of a local oscillator (≈ 4.6 GHz). Frequency stability of around 6 × l0 -12 is achieved at 1-s averaging using a 5-mm length cell. This result makes the technique attractive for developing a miniature frequency standard in thr microwave range. The third configuration exploits single-frequency counter-propagating beams with linear orthogonal polarizations. The ultrahigh-contrast subnatural-linewidth resonances can be observed when the longitudinal magnetic field is scanned around zero. The possible application is discussed of these resonances in vector atomic magnetometry.